Decision of the Classification of Students on the Basis of their Academic Grades - Azam, Muhammad; Aslam, Muhammad (Asian Journal of Empirical Research, 2013)
This paper presents the classification of students studying at Forman Christian College University Lahore using some commonly applied classification techniques namely classification trees (CT) using Gini function as splitting rule, linear discriminant analysis (LDA) and multinomial logistic regression (MLR). As per rule set by the university, each student is getting a final grade or label (taken as response variable) after passing through number of performances (taken as predictors). Motive behind the classification of students on the basis of their academic achievements is to build a model using the available information in favor of each student and predict the class labels for the new comers or fresh students.